Definitive Treatment With Microsurgical Clipping After Recurrence and Rerupture of Coiled Anterior Cerebral Artery Aneurysms. Issue 4 (14th May 2020) - Raper, Daniel M S; Rutledge, Caleb; Winkler, Ethan A; Abla, Adib A
Abstract: BACKGROUND: The extent of obliteration of ruptured intracranial aneurysms treated with coil embolization has been correlated with the risk of rerupture. However, many practitioners consider that a small neck remnant is unlikely to result in significant risk after coiling. OBJECTIVE: To report our recent experience with ruptured anterior cerebral artery aneurysms treated with endovascular coiling, which recurred or reruptured, requiring microsurgical clipping for subsequent treatment. METHODS: Retrospective review of patients with intracranial aneurysms treated at our institution since August 2018. Patient and aneurysm characteristics, initial and subsequent treatment approaches, and outcomes were reviewed. RESULTS: Six patients were included. Out of those 6 patients, 5 patients had anterior communicating artery aneurysms, and 1 patient had a pericallosal aneurysm. All initially presented with subarachnoid hemorrhage (SAH) and were treated with coiling. Recurrence occurred at a median of 7.5 mo. In 2 cases, retreatment was initially performed with repeat endovascular coiling, but further recurrence was observed. Rerupture from the residual or recurrent aneurysm occurred in 3 cases. In 2 cases, the aneurysm dome recurred; in 1 case, rerupture occurred from the neck. All 6 patients underwent treatment with microsurgical clipping. Follow-up catheter angiography demonstrated a complete occlusion of the aneurysm in all cases with the preservation of the parent vessel. CONCLUSION: Anterior cerebral artery aneurysms may recur after endovascular treatment, and even small neck remnants present a risk of rerupture after an initial SAH. Complete treatment requires a complete exclusion of the aneurysm from the circulation. Even in cases that have been previously coiled, microsurgical clipping can represent a safe and effective treatment option.